IMPROVING STUDENTS' MOTIVATION TO SPEAK ENGLISH THROUGH COLLABORATIVE LEARNING - Desi Sri Nurdianti, - (2008)
This paper entitled " Improving Students' Motivation to Speak English through Collaborative Leaming ''. This study was an experimental research aimed at finding out the effectiveness of Collaborative Leaming approach to improve students' motivation to speak English. This study involved the first grade students of SL TPN 1 Subang-Kuningan. There were four variables involved in the building of m..mmtlion, they....are initia_tktn .... .dlrection, intensity, and persiste.nce. which were identified in this study. The level of students' motivation was measured by administering the questionnaire to the students and the observation. The data were analyzed by using SPSS ver.12. The results show that students' motivation to speak English can be improved by Collaborative Learning. It is proved by the result of the score of motivation is significantly different between the pre- treatment and post-treatment at the coefficient too1=-2.709.